Using agent-based modelling to simulate the emission reduction potential of CCUS technologies in China under alternative policy packages - Changgen Dong; Zhuoluo Sun; Jingjing Jiang; Yang Yang (Environmental Research Letters)
Carbon capture, utilisation, and storage (CCUS) technologies are essential for achieving the 1.5 °C target. Predicting the emission reduction potential of CCUS technology is particularly important for countries to pursue carbon neutrality. However, the existing literature assessing the potential lacks consideration of the structural changes in industrial product demand and the trade-offs companies face between CCUS and traditional emission reduction technologies. This study used agent-based modelling (ABM) to simulate the emission reduction potential of CCUS in China’s thermal power, steel, cement, and chemical industries from 2022 to 2060 under scenarios of different carbon prices, subsidies, and technology progress rates. The possible biases of the traditional prediction model were corrected incorporating the structural changes in industrial product demand and the marginal abatement cost curves of traditional emission reduction technologies for the four major industries into the ABM model. The simulation results indicate that under each of the ten possible scenarios, China’s CCUS technologies will reach 100% penetration in the four mentioned industries by 2060, with the emission reduction potential fluctuating between 2222 and 1568 Mt of CO _2 (corresponding to 40% and 10% share of thermal power, respectively). The difference comes in the scaled-up threshold time point and the growth trend. Sensitivity analyses show that the carbon price affects changes in the emission reduction potential of CCUS technologies the most, while the impact of subsidies, rates of technological progress and oil prices were not significant. The stepped carbon price policy can effectively regulate and promote the expansion of CCUS emission reduction potential, which is worth considering for policymakers.